Sarcopenia: Molecular regulatory network for loss of muscle mass and function - Wu, Jiaxiang; Ding, Ping’an; Wu, Haotian; Yang, Peigang; Guo, Honghai; Tian, Yuan; Meng, Lingjiao; Zhao, Qun (Frontiers in Nutrition, 2023)
Skeletal muscle provides the basis for human function and plays a key role in motor and energy metabolism. Sarcopenia is characterized by progressive and systemic skeletal muscle disease, involving degenerative loss of muscle mass, strength and function. Therefore, sarcopenia results in debilitating physical weakness, functional disability, falls, morbidity, loss of independence, and death, which reduces the quality of life of patients. In recent years, sarcopenia has become the focus of in-depth research. Some molecular mechanisms have been described as the cause of sarcopenia, involving very different levels of muscle physiology. These mechanisms cover neuromuscular junction lesion, imbalance of protein synthesis and breakdown, satellite cells dysfunction, etc. In this review, we summarize the current view on molecular causes of sarcopenia development, in order to provide new ideas for future researchers to find valuable therapeutic targets and develop relevant prevention strategies.